Clarification of the lectotypification and some leaf characters of Pyrostria hystrix (Rubiaceae) - Bester, Stoffel P.; Steyn, Hester M. (Phytotaxa, 2026)
This contribution aims to clarify the correct typification of Pyrostria hystrix, showing that the accepted type is a lectotype rather than a holotype. A second-step lectotype is designated here to limit the typification to a single specimen. A further aim is to confirm the presence of domatia on the leaves of Pyrostria hystrix. Careful observation of the leaf morphology of numerous herbarium specimens, while revisiting the original Latin description of the leaves in the protologue, demonstrates that domatia are clearly present in this species, contrary to statements in later literature that explicitly report domatia as being absent. This highlights an important and diagnostic morphological character for the species that have been overlooked for decades.